Interrill erosion in shrub areas of Montesinho Natural Park: results of a rainfall simulation field study - Figueiredo, Tomás de (2012)
Vegetation communities known as shrubs cover around one third of the 750km2 of Montesinho Natural Park (PNM), located in NE Portugal. Those communities are grouped according to the dominant species in: “estevais” (Cistus ladanifer), “giestais” (Cytisus striatus), and “urzais” (Erica umbellata). In spite of the different phyto-sociological significance of each one of these groups, shrubs are stable elements of PNM landscape. Due to the large areas covered and also to their spatial distribution within PNM, shrubs play an important role in hydrological processes and soil protection in such a mountainous territory. Research leading to this presentation is part of a project designed and carried out to better know PNM shrub areas in terms of: (i) soil erosion risk; (ii) C sequestration in soil and vegetation strata; (iii) C dynamics in these systems. The presentation addresses to the first objective mentioned. Based on the vegetation map of PNM, an experimental site was selected to conduct field work, which accommodated in a short spatial range the design requirements: single soil type, a range of slope gradients, the three main vegetation communities. Field work comprised rainfall simulation runs with a portable spray-nozzle simulator calibrated for intensity and raindrop distribution and kinetic energy of simulated rain showers. Each run included: 30min rain over a square meter plot representing the vegetation community; runoff and washed sediment measurements in 10min steps; vegetation height and cover percentage; below and above ground vegetation biomass; organic soil horizon thickness; local average slope gradient; soil sampling down to 30cm depth; rock fragment contents. C content was determined by ignition loss in vegetation components, organic horizon and soil layers. Prior to runs soil was sampled for moisture content. Runs, 36 in total, were carried out according to experimental design; 3 vegetation communities (“estevais”, “giestais”, “urzais”), 3 topographic positions (slope gradient low, 5%; medium, 15%; high, 24%), 3 replicates. A run where vegetation and organic horizon were entirely removed was also carried out on each one of the vegetation communities and topographic positions. This allowed the assessment of potential erosional conditions. Global runoff and soil loss results rank vegetation communities as follows: “estevais” > “urzais” > “giestais”. Yet, “giestais” showed clearly lower runoff than the other, while “estevais” had clearly higher soil loss than the other. Average runoff, but not soil loss, increased with slope gradient. Vegetation and topographic effects on runoff and soil loss are not statistically significant. The general pattern for runoff is found in medium and high slope; vegetation communities rank differently in low slope (“urzais” > “estevais” > “giestais”). For soil loss, in medium and high slope the rank is the latter one; in low slope “estevais” lost more soil and “urzais” less. Canopy characteristics partly explain results obtained namely the size and distribution of leaves. Local factors also contribute to explain results, such as: organic horizon (thicker in “estevais” and shallower in “urzais”; decreasing thickness with slope increase), antecedent soil moisture (higher in “urzais” and lower in “giestais”) and estimated surface roughness (higher in “giestais” and “urzais”).